Pembelajaran Dengan Media Digital pada Madrasah Tsanawiyah Negeri 2 Aceh Besar: Wujud Madrasah Inovasi - Ida Mulyana (Indonesian Journal of Teaching and Teacher Education, 2023)
This study aims to explain the implementation of learning with digital media and its implementation efforts in a comprehensive manner. For this reason, this study uses a qualitative approach, with the research location at Madrasah Tsanawiyah Negeri 2 Aceh Besar. The results of the study show that at this madrasa, the learning method has begun to change from completely conventional methods to limited digital learning. This change began during the Covid-19 pandemic. After the Covid-19 pandemic, teachers and students are still using communication technology media, especially outside school hours. This method is used to complete learning that has not been completed or that students still need to ask the teacher. Comprehensive changes to the learning method to digital learning in this madrasa, are closely related to the establishment of this madrasa as an innovation madrasa, which is expected to school principals, teachers, students and parents of students to create innovations in increasing student achievement in both academic and non-academic dimensions. The academic and non-academic achievements that have been achieved by these madrasah students are also supported by the information and communication technology facilities available at the madrasa. As an innovation madrasa, the digital learning method with the blended method is an option. This selection has a positive impact, both based on learning theory and practical experience expressed by practitioners. To go towards the blended method, one class is set as an example.